Accelerated TLPD bonding of reliable IMCs micro joints using Cu–8Ni substrate under thermal gradient: Experiments and theoretical calculations - Yanqing Lai; Mingjie Wang; Donghui Zheng; Meiping Liu; Bao Chen; Jinmei Lv; Ning Zhao (Journal of Materials Research and Technology)
With the rapid development of the third-generation semiconductor power device towards high density, high performance, miniaturization and high temperature resistance, it is now urgent to develop a transient liquid phase diffusion (TLPD) bonding method with short bonding time and high reliability. In this study, a novel TLPD bonding method under thermal gradient (TG) with Cu–8Ni alloy as the substrate on the one side of Cu/Sn(40 μm)/Cu–8Ni micro joints was designed. Additionally, the microstructure, elemental characteristics, grain features and shear strengths of the bonded and aged micro joints were systematically investigated. The results indicated that the IMCs micro joints mainly consisted of fine and non-preferred orientation (Cu,Ni)6Sn5 grains could be successfully achieved after TLPD bonding under TG (TG-TLPD bonding) at 260 °C for only 9 min. The formed IMCs micro joints was mainly composed of fine (Cu,Ni)6Sn5 grains, which showed good heat-resistant abilities. Moreover, the shear strength of the formed IMCs micro joints was tested to be 58.69 MPa, which exhibited a slight reduction to 47.34 MPa following aging. Furthermore, the study of Ni-free Cu6Sn5 and Ni doped Cu6Sn5 crystals by theoretical analysis showed that the Young's, shear and bulk modulus of Ni doped Cu6Sn5 were slightly larger than those of Ni-free Cu6Sn5. Ni doping can promote the physical properties and crystal stability of Cu6Sn5 to a certain extent. The proposed Cu/solder/Cu–8Ni interconnection structure using TG-TLPD bonding was demonstrated to be a prospective approach, which drastically shorten bonding duration and obtained the IMCs micro joints with a good thermostability for advanced power device packaging.